Peer learning a pedagogical approach to enhance online learning: A qualitative exploration. (September 2016) - Raymond, Anita; Jacob, Elisabeth; Jacob, Darren; Lyons, Judith
Abstract: Background: Flexible online programs are becoming increasingly popular method of education for students, allowing them to complete programs in their own time and cater for lifestyle differences. A mixture of delivery modes is one way which allows for enhanced learning. Peer learning is another method of learning which is shown to foster collaboration and prepare healthcare students for their future careers. This paper reports on a project to combine peer and online learning to teach pharmacology to nursing students. Objectives: To explore undergraduate nursing student opinions of working in peer groups for online learning sessions in a pharmacology course. Design: A qualitative study utilising a self-reported questionnaire. Setting: A rural campus of an Australian university. Participants: Second year nursing students enrolled in a Bachelor of Nursing Program. Methods: A hard copy questionnaire was distributed to all students who attended the final semester lecture for the course. Content analysis of open-ended survey questions was used to identify themes in the written data. Results: Of the 61 students enrolled in the nursing subject, 35 students chose to complete the survey (57%). Students reported a mixed view of the benefits and disadvantages of peer online learning. Sixty 6% (66%) of students liked peer online learning, whilst 29% disliked it and 6% were undecided. Convenience and ease of completion were reported as the most common reason to like peer online learning, whilst Information Technology issues, communication and non-preferred learning method were reasons for not liking peer online learning. Conclusion: Peer online learning groups' acted as one further method to facilitate student learning experiences. Blending peer online learning with traditional face-to-face learning increases the variety of learning methods available to students to enhance their overall learning experience. Highlights: Peer learning minimised isolation commonly experienced by online students The majority of participants (66%) in this study liked the approach of learning online with their peers Blended peer online learning with traditional face-to-face learning enhanced the overall learning experience for students Convenience and ease of completion were reported as the most common reasons to like peer online learning